Tuboovarian Abscess due to Colonic Diverticulitis in a Virgin Patient with Morbid Obesity: A Case Report - Zafer Selçuk Tuncer; Gokhan Boyraz; Senem Özge Yücel; İlker Selçuk; Aslıhan Yazicioğlu (Case Reports in Medicine)
Since tuboovarian abscess is almost always a complication of pelvic inflammatory disease, it is rarely observed in virgins. A 30-year-old virgin patient presented with pelvic pain, fever, and vaginal spotting for the previous three weeks. Her abdominopelvic computed tomography scan revealed bilateral multiseptated cystic masses with prominent air-fluid levels suggesting tuboovarian abscesses. The sigmoid colon was lying between two tuboovarian masses, and its borders could not be distinguished from the ovaries. The patient was presumed to have bilateral tuboovarian abscesses which developed as a complication of the sigmoid diverticulitis. She was administered intravenous antibiotic therapy followed by percutaneous drainage under ultrasonographic guidance. She was discharged on the twenty second day with prominent clinical and radiological improvement. Diverticulitis may be a reason for development of tuboovarian abscess in a virgin patient. Early recognition of the condition with percutaneous drainage in addition to antibiotic therapy helps to have an uncomplicated recovery.